Excess Mg in situ powder addition for enhancing critical current density of ex situ MgB2 - Mohd Hapipi, Nurhidayah; Chen, Soo Kien; Shaari, Abdul Halim; Awang Kechik, Mohd Mustafa; Lim, Kean Pah; Tan, Kar Ban; Lee, Oon Jew; Miryala, Muralidhar (Springer, 2022)
In this work, ex situ MgB2 bulks were added with (1.5 Mg + 2B) and sintered in an attempt to enhance its intergrain connectivity. The addition was varied within the range of 0–50 wt.%, and the sintering was undertaken at 700 °C, 800 °C, and 1000 °C, respectively, for 1 h. Superconducting critical temperature, Tc of the samples was determined to be around 38 K as shown by the temperature dependence of susceptibility measurement. It was found that critical current density, Jc increased with the increased amount of the addition. Jc was further enhanced to 2 × 104A cm2 (0 T, 20 K) as the sintering temperature was raised. The increase of Jc is due to improved grain coupling as a result of in situ formation of MgB2, which fills the voids and connects the ex situ MgB2 grains. Additionally, the grain coupling was further strengthened by solid-state self-sintering at higher temperatures. The increment of Jc was accompanied by a narrower width of double-step transition of Tc attributable to a more complete MgB2 phase formation of the samples as the sintering temperature was increased.